Simulation and Modeling Time Response of Double Carrier Avalanche Photodiodes - Helmy Fitriawan (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2020)
Avalanche photodiodes (APDs) is a particularly sensitive semiconductor device that employs the photoelectric effect to convert light into electricity. APDs can be used in some typical applications, i.e. imaging, optical fiber communications, range finding, laser scanners and laser microscopy. In APDs, avalanche multiplication occurred due to impact ionization when the devices operating at high electric fields. Unfortunately, avalanche multiplication decreases the time response of APDs. The time response of an APD can be characterized by its current response which is represented by the mean current as a function of time. This paper discusses a method to estimate the time response of double-carrier multiplication avalanche photodiodes (APDs). The model, called The Random Path Length (RPL), generates random path length for a carrier to impact ionize and takes account of dead space distance into the calculation. Dead space distance is the minimum distance to travel by a carrier to gain the adequate energy to start first ionization. The RPL is applied into an ideal structure which is assumed has a dimensionless multiplication length, w = 1.0, with electrons and holes moving in constant speeds, ve = vh = v, for various dead spaces distances, d*. In this research, a computer code is generated to compute the mean impulse response, i(t), and the standard deviation, s(t), of APDs all as a function of time.